Risk association between human leucocyte antigens (HLA) and cervical neoplasia in Kenyan women - Muchiri, Lucy W.; Sekadde-Kigondu, Christine B.; Estambale, Benson B.; Temmerman, Marleen (KeSoBAP, 2012)
Background: Epidemiological studies have shown a strong link between human papilloma virus (HPV) infection and the development of cervical cancer. Certain Human Leucocyte Antigen (HLA) alleles may influence the susceptibility and outcome of HPV infection in carriers of those alleles. It is therefore important to investigate any potential protective and/or risk association between HLA and cervical neoplasia. Objective: To describe the risk association between HLA and cervical neoplasia in Kenyan women. Setting: Tigoni, Kiambu in Central Kenya. Method: Nested case-control study in a cervical cancer screening study. DNA was extracted from blood buffy coat cells. HLA typing was done by PCR to determine Class I and II gene frequencies. Results: In sixty six women (43 cases, 23 controls) aged 25-60 years (mean 36.98 (SD + 8.7), HLA class I B35 allele increased risk for cervical neoplasia, odds ratio (OR) 11.5 (95% CI 1.32-99.46). Individuals with HLA class II allele DR1 were 4 times more likely than controls to have a lesion OR=3.7 (95% CI 1.01-13.65) while HLA class I allele B35 increased by 22 times the risk of LSIL OR=22.5 (95% CI 2.30-219.89); HLA class I CW7 allele was protective , OR=0.1 (95% CI 0.003-0.72). HLA class I B7 allele increased by 5 times the likelihood of a lesion OR=5.2 (95% CI 10.6-25.13). HLA class II alleles DR1 and DQ5 increased risk for HSIL, OR 6.4 (95% CI 1.53-26.89) and 3.4 (95% CI 1.02-11.81) respectively. HLA class I BW6 appeared protective, OR 0.2 (95% CI 0.04-095).
Keywords: Cervical neoplasia; Human Leucocyte Antigen